A review of genus Agriocnemis larva (Odonata: Coenagrionidae) from Thailand including a description of the final stadium larva of Agriocnemis minima Selys, 1877 with supporting molecular (COI) data - Saetung, Tosaphol; Boonsoong, Boonsatien (Zootaxa, 2019)
The larva of Agriocnemis minima Selys, 1879 is described and illustrated for the first time, based on reared specimens collected from Thailand. Selected larvae of Agrioncnemis Selys, 1877 were matched with their adults by DNA barcoding. The mitochondrial COI gene (658 bp) of three species (A. minima, A. femina femina (Brauer, 1868), and A. pygmaea (Rambur, 1842)) occurring in Thailand was analysed to confirm the species identification and to determine the association between the larva and adult stages. The larva of A. minima can be distinguished from known species by the following combination of characteristics: 1) long simple setae on the antennomeres I and II, 2) protrusion of the male cerci as long as 0.5× the S10, and 3) tufts of spiniform setae on the lateral occiput margin and on the ventral view of the compound eyes. Comparisons to known larvae of Agriocnemis and those of some other subfamily Agriocnemidinae members are also provided.